Non-invasive embryo assessment: altered individual protein profile in spent culture media from embryos transferred at day 5 - Freis, Alexander; Rösner, Sabine; Marshall, Anne; Rehnitz, Julia; Horn, Kyra von; Capp, Edison; Dietrich, Jens Erik; Strowitzki, Thomas; Germeyer, Ariane (Reproductive sciences, 2021)
In order to improve ART outcome, non-invasive embryo assessment is gaining more and more attention. Therefore, the aim of this study is to determine the consecutive implantation potential via the secretome between blastocysts with or without implantation and to analyse possible interactions between these differentially expressed proteins. In this prospective study, 69 spent culture media from blastocysts transferred at day 5 were collected from patients undergoing IVF/ICSI treatment in a single IVF centre between April 2015 and November 2018 after informed consent and analysed individually. Exclusion criteria were the absence of informed consent, PCOS, endometriosis and maternal age > 42 years. Dependent on the treatment outcome, media were subsequently divided into two groups: from embryos who implanted successfully (n = 37) and from embryos without implantation (n = 32). Ninety-two proteins were measured simultaneously using the proximity extension assay (PEA) technology with the Olink® CVD III panel employing oligonucleotide-labelled antibodies. Statistical analysis was performed using the Kolmogorov-Smirnov test, Student’s t test, the Mann-Whitney U test and Fisher’s exact test. Media from implanted blastocysts showed significantly higher expression of EPHB4, ALCAM, CSTB, BMH, TIMP4, CCL24, SELE, FAS, JAM-A, PON3, PDGF-A, vWF and PECAM-1 compared with media from blastocysts without subsequent implantation. The highest relative expression change could be demonstrated for PECAM-1 and TIMP4. PECAM-1, SELE and vWF were co-expressed. Especially EPHB 4, SELE, ALCAM, MCP-1, CCL24, FAS, JAM-A and PDGF-A have already been described in early embryonic development and metabolism. Therefore, these proteins together with PECAM-1 indicate possible biomarkers for non-invasive embryo assessment in the future. However, due to the innovative methodology, defining a threshold for the use as biomarkers remains to be assessed.